Computers, communication and confidentiality: tales of Baron Munchausen. Issue 1 (January 1996) - Wright, B; Bhugra, D; Booth, S J
Abstract : The aim was to examine the use of computer and paper based systems in accident and emergency (A&E) departments in the management of patients who are frequent attenders. More than half of the A&E consultants in the Thames regions who were sent a questionnaire responded (44 of the 80). 82% of the respondents use such systems predominantly to monitor violent patients, those with Munchausen syndrome, and children on the "at risk" register. Systems currently in use fail to fulfil many of the functions that would be required of an ideal system. When using computers to store and communicate clinical data, several ethical problems were identified but these appeared to be outweighed by the practical need and were also present with paper based systems. Safeguards could also be built into computer based systems to reduce some of the ethical problems. Computer systems should be deliberately chosen and implemented in response to a specific management problem. The potential benefits should be weighed against possible damaging side effects, such as a breach of confidentiality.